ANALISIS FAKTOR EKOLOGIS VEGETASI MANGROVE DI NEGERI ETI TELUK PIRU KABUPATEN SBB - Mega M.S. Badu; Fanny Soselisa; Anjela. Sahupala (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
This study aims to determine the types of mangrove vegetation and the factors where mangroves grow in the land of Eti, Teluk Piru, West Seram Regency. The methods used in the measurement and observation in this study were descriptive and field surveys. Based on the results of mangrove research in the country of Eti, Teluk Piru, West Seram Regency, the types of vegetation that make up the mangrove ecosystem at the research site are: Sonneratia alba, Rhizophora apiculata, Rhizophora stylosa, Bruguiera gymnorrhyza, Bruguiera cylindrica, Avicennia officinalis, Xylocarpus granatum, Nypa fruticaria. agallocha and Scyphiphora hydrophyllacea and the measurement results of environmental parameters that affect mangroves, namely. Temperature: the lowest temperature range is 27oC to the highest temperature is 33oC. Salinity: the lowest salinity level is 21 ppt to the highest salinity is 33 ppt. The degree of acidity (pH) of water: the range of the lowest water pH is 5.5 to the highest temperature 8. The degree of acidity (Ph) of the soil: the range of the lowest water pH is 5 to the highest temperature 8. Subsrak: the condition of the soil at the study site has a type of substrate mud up to sandy mud. DO: the average DO front is 2.9 mg/1 and the average DO back is 2.8 mg/1 in the results obtained the average DO value is 5.3 mg/l. mud thickness: the average thickness of the front mud is 43 cm, the average thickness of the middle mud is 31 cm and the average thickness of the rear mud is 29 cm.